The determinant of educational mismatch and its correlation to wages - Ferry Maurist Sitorus; Padang Wicaksono (Department of Development Economics, Universitas Sriwijaya, 2020)
The mismatch between educational and occupational qualifications is an issue that still frequently occurs in the Indonesian job market. This study aims to sudy the probability of educational mismatch in workers and how it was related to the wages received. The data used in this study was gained from the National Labor Force Survey (Sakernas) August 2019. The unit of analysis used are workers that have status as labor/employee/employees who are 15 years old and above. Contingency coefficient analysis was used to investigate the correlation between mismatch and workers’ wages, and multinomial logistic regression analysis was used to investigate the determinants of educational mismatch. The results showed that educational mismatch in the Indonesian labor market was still quite high, in which from a total sample of 178.085 workers / laborers, 25,79% were overeduaction and 17,98% were undereducation. The results of the contingency coefficient showed that there was a correlation between educational mismatch status and workers' wages. Then based on the result of the multinomial logistic regression test, it was found that workers with overeducation status had a greater chance of those who had a longer length of schooling, who were male and urban, while workers with undereducation status had a greater chance of those with shorter school years, who were female and live in rural areas.